Performance of IPO during hot and cold market / Nur Shahirah Abdul Aziz - Abdul Aziz, Nur Shahirah (2008)
This paper examines the short-run performance of 30 Malaysian IPOs issued during the period 1996 to 2001. The performance of IPOs was analyzed based on the different economic period namely hot and cold markets. A hot market was characterized by an unusually high volume of offering and high number of IPOs issued. In contrast, a cold market has much lower issuance. The performances of IPOs have been analyzed based on market adjusted initial return as adopted previous studies to see the performance in different economic condition. In order to determine the short-run performance of IPO, the five interval periods selected are first day, first week, first month, third month and sixth month upon listing. After analyzed both market conditions, this study documents an average first day initial return of 11.44%. The findings show difference in different economic condition. Over the short run period, IPO recorded 31.82% abnormal return in the hot market for the last sixth month. The finding shows a significant difference in the mean initial return under different economic condition. In the hot market, Malaysian IPOs recorded a high initial return which is 32.06% than in the cold market -8.82%. However, for the short run performance in the cold market, the result was recorded negative return of -8.82% and 3.09% in the first day and first week. The rest of interval period still shows the positive return in cold market.